Investigation of Physicians' Perspectives of Drug Promotional Activities - OKUYAN, BETÜL; SANCAR, MESUT; AY, NADİYE PINAR (AVES PRESS LTD, 2016)
Objective: Pharmaceutical company promotional activities (PCPAs) are listed among the factors that influence the prescribing behavior of physicians. This study aimed to determine the opinions of family physicians (FPs) and specialist physicians (SP) on the impact of these activities. Methods: A survey comprising 1062 FPs working in primary health centers and 562 SPs working in public hospitals at different cities in Turkey was conducted. The questions thoroughly evaluated physicians' approaches toward PCPAs, particularly drug promotional activities. Answers were evaluated with respect to the demographic and occupational characteristics of physicians. Results: Based on the statements of participants, 82.8% of FPs and 88.6% of SPs declared that physicians always or sometimes are influenced by PCPAs. Percentage of SPs who declared themselves as always or sometimes influenced by PCPAs was significantly higher than that of FPs (p=0.006). Overall, 56.3% of FPs and 43.3% of SPs were visited >5 times during the last 5 working days by pharmaceutical sales representatives. When considering features of drugs prescribed after PCPAs, both FPs and SPs declared that these drugs were cheaper (52.8% and 47.8%, respectively) and safer (52.7% and 49.3%, respectively) than their alternatives. Conclusion: Physicians' statements showed that they were often visited by pharmaceutical sales representatives and highly influenced by PCPAs. Differences with respect to the experiences and approaches of FPs and SPs regarding this issue are critical factors warranting careful consideration of a rational PCPA implementation.
Keywords: Pharmaceutical company; promotional activities; pharmaceutical sales representatives; family physician; specialist physician